Clustering Administrative City Based On Indicator Livable City in West Java Province - Rilansari, Valendya (Universitas Komputer Indonesia (UNIKOM), 2022)
As the population increases every year then a place to live, especially with livable conditions. Cities in the world are trying realizing the city with the concept of a livable city for residents to live comfortably in that city. In Indonesia, planning the city that it can inhabited. Based on the livable city indicators, there are still many cities in Indonesia that have not achieve it. In this case, especially for the cities in West Java Province has a vision as a city comfortable, need to apply the concept of the city livable in realizing the condition of the city. Furthermore, in this study an analysis was carried out to find out which city groups needed prioritized in the realization of a livable city in West Java Province. This study uses cluster analysis of city grouping with various methods in the hierarchical method using R Programming. Finally, this research will produce a group of cities that will be prioritized for accelerating its realization by improving aspects that are still lacking in development according to the indicators of livable city.